Study the Role of Cell Free DNA in the Diagnosis of Hepatocellular Carcinoma, an Egyptian Study - Radwan, Noha Hassan; Abdelkhalik, Hadeer Ali; Elgayar, Dina Farouk; Elsharkawy, Marwa Mahmoud (Asian Pacific Journal of Cancer Biology, 2022)
Background and objective: Hepatocellular carcinoma (HCC) is a primary malignancy of the liver. Since the conventional tissue biopsy and AFP have limited value, a new promising diagnostic method” liquid biopsy” has emerged. Cell free DNA is one of the liquid biopsy corner stones along with circulating tumor cells. Aim of the work: The study aims to evaluate the role of cf-DNA in the prediction of HCC. Subjects and methods: Eighty newly diagnosed HCC cases and seventy seven apparently healthy individuals were recruited from the National Cancer Institute, Cairo University. Cf-DNA level is measured by Qubit fluorometer assay and AFP was measured by ELISA for control. Comparisons between quantitative variables were done using the non-parametric Kruskal-Wallisand Mann-Whitney. Correlation between quantitative variables were done using Spearman correlation coefficient and a ROC curve was constructed with area under curve analysis performed to detect best cut off value of cf-DNA and AFP for detection of HCC. Results: The median cf-DNA and AFP levels were statistically significant higher in HCC patients (0,11ng/µl and 160.9 ng/ml respectively) than in control group (0.04 ng/ µl and 1.30 ng/ml respectively). Upon plotting ROC curve, cf-DNA and AFP gave a sensitivity of 78% and 93.7% respectively, a specificity of 59.7% and 92.2% respectively. The diagnostic value of cf-DNA in combination with AFP level has slightly improved the specificity (96.1%) on the expense of the sensitivity which was decreased (69.5%). Conclusion: Cf-DNA plays a role in the prediction of HCC but still AFP has the upper hand in the diagnosis of HCC in Egyptian population. Liquid biopsy still hasits own limitations. The techniques of colleting’ liquid”, and detection of cf-DNA must be standardized.